2012
DOI: 10.3354/meps09526
|View full text |Cite
|
Sign up to set email alerts
|

Denitrification: an ecosystem service provided by salt marshes

Abstract: We hypothesized that denitrification rates, as an N removal process, would be enhanced in salt marsh rhizosediments as compared to sediments without vegetation (bare mudflats). Denitrification rates (measured by the 15 N-isotope pairing technique), potential nitrification, and nutrient fluxes were seasonally quantified in a Spartina maritima salt marsh and in adjacent bare mudflats. Potential nitrification rates were significantly higher in autumn and winter, but there were no significant differences between t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(20 citation statements)
references
References 84 publications
1
19
0
Order By: Relevance
“…Results from the present study confirm the service provided by rooted aquatic plants as benthic filters of nitrogen in eutrophic conditions (Sousa et al 2012;Nizzoli et al 2014). Sediments with V. spiralis removed nearly one order of magnitude more N compared to bare sediments, regardless the level of organic enrichment.…”
Section: Discussionsupporting
confidence: 85%
“…Results from the present study confirm the service provided by rooted aquatic plants as benthic filters of nitrogen in eutrophic conditions (Sousa et al 2012;Nizzoli et al 2014). Sediments with V. spiralis removed nearly one order of magnitude more N compared to bare sediments, regardless the level of organic enrichment.…”
Section: Discussionsupporting
confidence: 85%
“…This pathway is achieved through denitrification and anammox, processes that operate in hypoxic to anoxic environments (Canfield et al, 2010). Recent results have pointed at the same ecosystem components mediating high nutrient burial rates in coastal ecosystems, seagrass meadows, oyster reefs, mangrove and saltmarshes (e.g., Valiela and Cole, 2002;Sousa et al, 2012), as important vaults for removal of reactive nitrogen as N 2 gas emitted to the atmosphere. Denitrification rates in seagrass meadows are reported to be about fivefold greater than those in unvegetated sediments (Reynolds et al, 2016;Eyre et al, 2016;Zarnoch et al, 2017), while oyster reefs also support much higher denitrification rates than adjacent sediments free of such components (Kellogg et al, 2014;Caffrey et al, 2016;Smyth et al, 2016).…”
Section: Interventions To Enhance Nitrogen Emissions As Nmentioning
confidence: 99%
“…In oyster reefs, however, anammox rates have not yet been reported, to the best of our knowledge. Mangroves (Cao et al, 2017;Reis et al, 2017) and salt-marshes (Sousa et al, 2012) have also been reported to support very high anammox and denitrification rates, particularly when receiving high nitrate inputs (Koop-Jakobsen and Giblin, 2010;Reis et al, 2017). Hence, a high capacity for removal of reactive nitrogen, through both burial and, particularly, removal of reactive nitrogen as N 2 gas, is a key, but hitherto insufficiently realized ecosystem service of seagrass meadows (Reynolds et al, 2016;Zarnoch et al, 2017), oyster reefs (Cerco and Noel, 2007;Kellogg et al, 2014;Caffrey et al, 2016;Smyth et al, 2016), mangroves (Valiela and Cole, 2002;Cao et al, 2017;Reis et al, 2017) and salt-marshes (Valiela and Cole, 2002;Koop-Jakobsen and Giblin, 2010;Sousa et al, 2012).…”
Section: Interventions To Enhance Nitrogen Emissions As Nmentioning
confidence: 99%
“…Estuaries are highly productive habitats (Dolbeth et al., ; Hicks et al., ; Kennish, ) and functionally important areas (e.g., Sousa, Lillebø, Pardal, & Caçador, ; Sousa, Lillebø, Risgaard‐Petersen, Pardal, & Caçador, ). They are generally characterized by low diversity, constrained by local environmental conditions (Dolbeth et al., ; Hicks et al., ; Kennish, ), such that the introduction of new species that have different traits to the recipient community can have a disproportionate effect on the functioning of the ecosystem (Darrigran & Damborenea, ; Simberloff et al., ; Stachowicz & Byrnes, ).…”
Section: Introductionmentioning
confidence: 99%